Free radical scavenging and antioxidant activities of flavonoids extracted from the radix of Scutellaria baicalensis Georgi - Gao, Zhonghong; Huang, Kaixun; Yang, Xiangliang; Xu, Huibi (Biochimica et biophysica acta, 1999)
Free radical scavenging and antioxidant activities of baicalein, baicalin, wogonin and wogonoside, the four major flavonoids in the radix of Scutellaria baicalensis Georgi, were examined in different systems. ESR results showed that baicalein and baicalin scavenged hydroxyl radical, DPPH radical and alkyl radical in a dose-dependent manner, while wogonin and wogonoside showed subtle or no effect on these radicals. Ten μmol/l of baicalein and baicalin effectively inhibited lipid peroxidation of rat brain cortex mitochondria induced by Fe 2+-ascorbic acid, AAPH or NADPH, while wogonin and wogonoside showed significant effects only on NADPH-induced lipid peroxidation. In a study on cultured human neuroblastoma SH-SY5Y cells system, it was found that 10 μmol/l of baicalein and baicalin significantly protected cells against H 2O 2-induced injury. Baicalein was the most effective antioxidant among the four tested compounds in every system due to its o-tri-hydroxyl structure in the A ring. Compared with a well-known flavonoid, quercetin, the antioxidant activity of baicalein was lower in DPPH or AAPH system, but a little higher in those systems which might associate with iron ion. These results suggest that flavonoids in the radix of Scutellaria baicalensis with o-di-hydroxyl group in A the ring, such as baicalein and baicalin, could be good free radical scavengers and might be used to cure head injury associated with free radical assault.